Treatment and management of primary antibody deficiency: German interdisciplinary evidence‐based consensus guideline. Issue 10 (9th September 2020) - Hanitsch, Leif; Baumann, Ulrich; Boztug, Kaan; Burkhard‐Meier, Ulrike; Fasshauer, Maria; Habermehl, Pirmin; Hauck, Fabian; Klock, Gerd; Liese, Johannes; Meyer, Oliver; Müller, Rainer; Pachlopnik‐Schmid, Jana; et al.
Abstract: This evidence‐based clinical guideline provides consensus‐recommendations for the treatment and care of patients with primary antibody deficiencies (PADs). The guideline group comprised 20 clinical and scientific expert associations of the German, Swiss, and Austrian healthcare system and representatives of patients. Recommendations were based on results of a systematic literature search, data extraction, and evaluation of methodology and study quality in combination with the clinical expertise of the respective representatives. Consensus‐based recommendations were determined via nominal group technique. PADs are the largest clinically relevant group of primary immunodeficiencies. Most patients with PADs present with increased susceptibility to infections, however immune dysregulation, autoimmunity, and cancer affect a significant number of patients and may precede infections. This guideline therefore covers interdisciplinary clinical and therapeutic aspects of infectious (e.g., antibiotic prophylaxis, management of bronchiectasis) and non‐infectious manifestations (e.g., management of granulomatous disease, immune cytopenia). PADs are grouped into disease entities with definitive, probable, possible, or unlikely benefit of IgG‐replacement therapy. Summary and consensus‐recommendations are provided for treatment indication, dosing, routes of administration, and adverse events of IgG‐replacement therapy. Special aspects of concomitant impaired T‐cell function are highlighted as well as clinical data on selected monogenetic inborn errors of immunity formerly classified into PADs (APDS, CTLA‐4‐, and LRBA‐deficiency). Abstract : An evidence‐ and consensus‐based clinical guideline for the treatment and care of patients with primary antibody deficiencies (PADs) was developed by 20 medical societies from Austria, Germany, and Switzerland. Recommendations cover Ig replacement therapies as well as other aspects of the management of infectious and non‐infectious manifestations.